Comparative satellite DNA mapping in species of the genus Prochilodus (Teleostei, Characiformes) and its evolutionary implications - Dos Santos, Rodrigo Zeni [UNESP]; Goes, Caio Augusto Gomes [UNESP]; Stornioli, José Henrique Forte [UNESP]; Sassi, Francisco de Menezes Cavalcante; de Moraes, Renata Luiza Rosa; Dergam, Jorge Abdala; Porto-Foresti, Fábio [UNESP]; de Bello Cioffi, Marcelo; Utsunomia, Ricardo [UNESP] (Canadian Science Publishing, 2025)
Satellite DNA (satDNA) sequences are dynamic components of the eukaryotic genome that can play significant roles in species diversification. The Prochilodontidae family, which includes 21 Neotropical fish species, is characterized by a conserved karyotype of 2n = 54 biarmed chromosomes, with variation in some species and populations regarding the presence or absence of B chromosomes. This study aimed to investigate whether the chromosomal distribution of specific satDNA sequences is conserved among three Prochilodus species (Prochilodus lineatus, Prochilodus costatus, and Prochilodus argenteus) regarding organization and number of loci, and to compare their genomes using comparative genomic hybridization (CGH). Our results demonstrated that most satDNA sequences share a similar distribution pattern across the three species, and CGH analysis corroborated that their karyotypes are very similar in terms of repetitive DNA distribution. We also identified a potential CENP-B box sequence within PliSat01, a satDNA located in the pericentromeric region of all analyzed species. In contrast, PliSat04 and PliSat14 displayed differential locations and variations in the number of loci per genome, underscoring the dynamic nature of repetitive sequences even in species with otherwise highly conserved genomes. These findings represent the first evidence of karyotype diversification in Prochilodus, highlighting the evolutionary dynamism of satDNA sequences.
Keywords: B chromosomes; comparative genomic hybridization; cytogenomics; fluorescence in situ hybridization; satDNA evolution